Caveolae as Potential Hijackable Gates in Cell Communication - Dudãu, Maria; Codrici, Elena; Tanase, Cristiana; Gherghiceanu, Mihaela; Enciu, Ana-Maria; Hinescu, Mihail E. (Frontiers in Cell and Developmental Biology, 2020)
Caveolae are membrane microdomains described in many cell types involved in endocytocis, transcytosis, cell signalling, mechanotransduction, and ageing. They are found at the interface with the extracellular environment and are structured by caveolin and cavin proteins. . Caveolae and caveolins mediate transduction of chemical messages via signalling pathways, as well as non-chemical messages, such as stretching or shear stress. Various pathogens or signals can hijack these gates, leading to infectious, oncogenic and even caveolin-related diseases named caveolinopathies. By contrast, preclinical and clinical research have fallen behind in their attempts to hijack caveolae and caveolins for therapeutic purposes. Caveolae involvement in human disease is not yet fully explored or understood and, of all their scaffold proteins, only caveolin-1 is being considered in clinical trials as a possible biomarker of disease. This review briefly summarizes current knowledge about caveolae cell signalling and raises the hypothesis whether these microdomains could serve as hijackable “gatekeepers” or “gateways” in cell communication. Furthermore, because cell signalling is one of the most dynamic domains in translating data from basic to clinical research, we pay special attention to translation of caveolae, caveolin, and cavin research into clinical practice